Land management explains major trends in forest structure and composition over the last millennium in California's Klamath Mountains - Knight, Clarke A; Anderson, Lysanna; Bunting, M Jane; Champagne, Marie; Clayburn, Rosie M; Crawford, Jeffrey N; Klimaszewski-Patterson, Anna; Knapp, Eric E; Lake, Frank K; Mensing, Scott A; Wahl, David; Wanket, James; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
SignificanceWe provide the first assessment of aboveground live tree biomass in a mixed conifer forest over the late Holocene. The biomass record, coupled with local Native oral history and fire scar records, shows that Native burning practices, along with a natural lightning-based fire regime, promoted long-term stability of the forest structure and composition for at least 1 millennium in a California forest. This record demonstrates that climate alone cannot account for observed forest conditions. Instead, forests were also shaped by a regime of frequent fire, including intentional ignitions by Native people. This work suggests a large-scale intervention could be required to achieve the historical conditions that supported forest resiliency and reflected Indigenous influence.